Mother's Behavior in Breastfeeding after the Covid-19 Pandemic: a Cross Sectional Study - Reni Yuli Astutik; Nining Istighosah; Suci Anggraeni; Devy Putri Nursanti; Eri Puji Kumalasari (Universitas STRADA Indonesia, 2023)
Background: Research related to the implementation of breastfeeding guidelines after the COVID-19 pandemic in healthy breastfeeding mothers is still minimal, even though the mother's behavior in implementing breastfeeding guidelines correctly can ensure the safety of breastfeeding. Purpose: This study aims describe the behavior of mothers in breastfeeding during and after COVID-19 pandemic. Methods: This study used a cross-sectional design. The sample in this study were breastfeeding mothers who had babies aged less than 6 months who met the inclusion criteria and obtained a total of 94 respondents. The research instrument used a questionnaire. Mother's behavior in breastfeeding is categorized into good, moderate and sufficient categories. Data analysis used the wilcoxon signed ranks test to compare behavior during and after the COVID-19 pandemic. Results: During the pandemic, the behavior of mothers in the moderate category was more than the good or sufficient category, which was 42.6%. Meanwhile, after the pandemic, there was no maternal behavior in the sufficient category, while the good category was more than the moderate category, which was 71.3%. The Wilcoxon Rank Test results obtained p-value=0.000, there was a significant difference between the behavior of mothers in breastfeeding during and after the COVID-19 pandemic. Conclusion: The covid-19 pandemic period for breastfeeding mothers is an external stimulus, it is hoped that mothers can make changes to the right breastfeeding pattern in accordance with health protocols as an effort to control and prevent the spread of covid-19 during the breastfeeding process, because the benefits of breastfeeding far exceed the potential for COVID-19 transmission.